A scale analysis model for film boiling heat transfer on a vertical flat plate with wide applicability. (November 2015) - Das, Dipak Chandra; Ghosh, Koushik; Sanyal, Dipankar
Highlights: A scale analysis is carried out to study film boiling of vertical flat plate. High superheat and low superheat cases have been separately treated with appropriate vaporization criteria. Nusselt number shows a dependence on Jakob superheat and subcooling number for different cases. The radiation is important beyond a Jakob superheat number of 1–1.2. More than 96% experimental data lies within ±20% error band of those obtained from scale analysis. Abstract: A model has been developed in present work, for a vertical flat plate under film boiling condition, based on scale analysis. The saturated and subcooled film boiling have been analyzed from heat and mass transfer consideration and appropriate vaporization criteria. The model takes care of natural convection and forced convection mode of heat transfer for subcooled case, while the saturated film boiling is treated with an assisting convection mode. The interfacial wave length is incorporated into the length scale and the effect of radiation heat transfer is accounted in the model. Expressions for Nusselt number have been developed for different situations. The present model recovers the Bromley scale for natural convection under saturated condition. The heat transfer characteristic is shown for relevant non-dimensional numbers pertaining to film boiling for various cases. A wide set of existing experimental data with ranges of wall superheat 260–1200 °C, liquid subcooling 0–50 °C and flow velocity 0–2.65 m/s have been systematically utilized to arrive at the model closure.